Non-performing loan regimes in banking regulation - Leesurakarn, Saveethika (2021)
Non-performing loans (NPLs) have recently been perceived worldwide as a troubling potential cause of vulnerabilities and a threat to national and global financial systems, undermining core banking-sector functions including lifeblood financing of economies. NPLs constitute a key determiner of banks’ profitability and stability because the level of NPLs substantially affects bank lending behaviours and bank internal risk management, which chiefly include loan-loss provisioning (LLP) and capital charges. There is therefore a clear need to monitor and regulate the level of banks’ NPLs. This thesis examines regimes governing NPLs in Thailand in the respects of LLP and capital requirements. Most Thai banking regulation covering NPL regimes has implemented international standards, in particular those of Basel III and IFRS 9. The consequence of this transnational legal borrowing has clearly led to a significant increase in banks’ provisioning and capital charges. This thesis therefore seeks to investigate whether the legal frameworks of LLP and capital requirements genuinely can assist in reducing and / or preventing the threats to financial stability caused by higher NPL ratios. It does so by applying a dynamic functionalist approach to assess whether the novel NPLs regime do in fact achieve their functional goals in diminishing the threats posed by NPLs to Thailand’s financial stability. This thesis also adopts legal transplantation theory in banking regulation to demonstrate how and how effectively international standards have been transplanted into Thailand’s banking regulations. The thesis argues that the Thai financial regulatory system of NPLs is unable to function fully effectively to prevent instability arising from NPLs because of what might be called less than wholly appropriate appropriation of international standards into the context of the Thai financial system has had unintended and unwanted results. The transplantation has caused problems in the practices of banks in terms of the application of new ...